2020
DOI: 10.1056/nejmoa1914609
|View full text |Cite|
|
Sign up to set email alerts
|

Tucatinib, Trastuzumab, and Capecitabine for HER2-Positive Metastatic Breast Cancer

Abstract: BACKGROUND Patients with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer who have disease progression after therapy with multiple HER2-targeted agents have limited treatment options. Tucatinib is an investigational, oral, highly selective inhibitor of the HER2 tyrosine kinase. METHODS We randomly assigned patients with HER2-positive metastatic breast cancer previously treated with trastuzumab, pertuzumab, and trastuzumab emtansine, who had or did not have brain metastases, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
752
0
38

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 931 publications
(871 citation statements)
references
References 25 publications
14
752
0
38
Order By: Relevance
“…The HER2CLIMB trial evaluated the addition of tucatinib to trastuzumab and capecitabine in patients with HER2-positive breast cancer previously treated with trastuzumab, pertuzumab, and T-DM1. The one-year PFS rate was 33.1% for the tucatinib-containing regimen and 12.3% for the control regimen (HR of 0.54, 95% CI of 0.42-0.71; p < 0.001), and the median PFS rates were 7.8 and 5.6 months, respectively, with the primary end point thus being met [56].…”
Section: Pan-her Tkismentioning
confidence: 94%
“…The HER2CLIMB trial evaluated the addition of tucatinib to trastuzumab and capecitabine in patients with HER2-positive breast cancer previously treated with trastuzumab, pertuzumab, and T-DM1. The one-year PFS rate was 33.1% for the tucatinib-containing regimen and 12.3% for the control regimen (HR of 0.54, 95% CI of 0.42-0.71; p < 0.001), and the median PFS rates were 7.8 and 5.6 months, respectively, with the primary end point thus being met [56].…”
Section: Pan-her Tkismentioning
confidence: 94%
“…These characteristics are consistent with tucatinib's observed safety and activity in early clinical trials in patients with HER2 þ MBC, including the phase I ONT-380-005 study (NCT02025192) in combination with trastuzumab or trastuzumab and capecitabine (26) and the phase I ONT-380-004 study (NCT01983501) combining tucatinib with Ado-Trastuzumab Emtansine in patients with HER2 þ MBC with or without brain metastases (28). Furthermore, the outcome of an international, randomized, double-blind trial comparing the combination of tucatinib plus trastuzumab and capecitabine to placebo plus trastuzumab and capecitabine was recently reported (47). The results of this trial demonstrated the addition of tucatinib to trastuzumab and capecitabine resulted in better progression-free survival and overall survival outcomes in patients with heavily pretreated HER2-positive MBC, including those with brain metastases.…”
Section: Mct First Disclosuresmentioning
confidence: 99%
“…The current HER2-targeted therapies (trastuzumab, pertuzumab and lapatinib) have been approved for clinical treatment of HER2-positive BC and largely improved prognosis of HER2-positive cases [34]. Unfortunately, the unavoidable side effects induced by the therapies and drug resistance are always accompanied during the therapeutic period and have become the biggest challenge in clinical application [35,36].…”
Section: Discussionmentioning
confidence: 99%